Optimalisasi Pengembalian Dana pada Kesalahan Transfer - Nainggolan, Valen; Djajaputra, Gunawan (Universitas Ekasakti, 2024)
The mechanism of fund reimbursement in cases of transfer errors is crucial in maintaining customer trust and satisfaction in banking services. This study aims to investigate and propose optimal steps to enhance the effectiveness of fund reimbursement mechanisms. The research methodology involves literature analysis and case studies to understand key challenges and best practices in the banking industry. Findings indicate that transfer errors can occur due to various factors, including human error, system glitches, or fraudulent activities. To optimize fund reimbursement mechanisms, a holistic approach is required, encompassing improvements in internal processes, enhanced transparency, and communication with customers, as well as the implementation of advanced technologies such as anomaly detection and automated verification. The implications of this research underscore the importance for banks to continuously improve their systems and procedures in handling transfer errors, thereby enhancing customer trust and maintaining corporate reputation. This study provides practical guidance for banks in addressing challenges related to transfer errors and ensuring swift and accurate fund reimbursements to customers.